Carrier multiplication in silicon nanocrystals: ab initio results - Marri, Ivan; Govoni, Marco; Ossicini, Stefano (Beilstein Journal of Nanotechnology, 2015)
One of the most important goals in the field of renewable energy is the development of original solar cell schemes employing new materials to overcome the performance limitations of traditional solar cell devices. Among such innovative materials, nanostructures have emerged as an important class of materials that can be used to realize efficient photovoltaic devices. When these systems are implemented into solar cells, new effects can be exploited to maximize the harvest of solar radiation and to minimize the loss factors. In this context, carrier multiplication seems one promising way to minimize the effects induced by thermalization loss processes thereby significantly increasing the solar cell power conversion. In this work we analyze and quantify different types of carrier multiplication decay dynamics by analyzing systems of isolated and coupled silicon nanocrystals. The effects on carrier multiplication dynamics by energy and charge transfer processes are also discussed.
Keywords: carrier multiplication; nanocrystals; silicon; solar cells

(untitled) - Ossicini, S.; Bisi, O.; Degoli, E.; Marri, I.; Iori, F.; Luppi, E.; Magri, R.; Poli, R.; Cantele, G.; Ninno, D.; Trani, F.; Marsili, M.; et al. (J. Nanosci. Nanotechnol., 2008)

(untitled) - Iori, F.; Degoli, E.; Luppi, E.; Magri, R.; Marri, I.; Cantele, G.; Ninno, D.; Trani, F.; Ossicini, S. (J. Lumin., 2006)

(untitled) - Guerra, R.; Marri, I.; Magri, R.; Martin-Samos, L.; Pulci, O.; Degoli, E.; Ossicini, S. (Phys. Rev. B, 2009)

(untitled) - Iori, F.; Degoli, E.; Magri, R.; Marri, I.; Cantele, G.; Ninno, D.; Trani, F.; Pulci, O.; Ossicini, S. (Phys. Rev. B, 2007)

(untitled) - Priolo, F.; Gregorkiewicz, T.; Galli, M.; Krauss, T. F. (Nat. Nanotechnol., 2014)

(untitled) - Shockley, W.; Queisser, H. J. (Appl. Phys. Lett., 1961)

(untitled) - Klimov, V. I.; Mikhailovsky, A. A.; Xu, S.; Malko, A.; Hollingsworth, J. A.; Leatherdale, C. A.; Eisler, H.-J.; Bawendi, M. G. (Science, 2000)

(untitled) - Beard, M. C. (J. Phys. Chem. Lett., 2011)

(untitled) - Benisty, H.; Sotomayor-Torrès, C. M.; Weisbuch, C. (Phys. Rev. B, 1991)

(untitled) - Nozik, A. J. (Phys. E (Amsterdam, Neth.), 2002)

(untitled) - Califano, M.; Zunger, A.; Franceschetti, A. (Nano Lett., 2004)

(untitled) - Ellingson, R. J.; Beard, M. C.; Johnson, J. C.; Yu, P.; Micic, O. I.; Nozik, A. J.; Shabaev, A.; Efros, A. L. (Nano Lett., 2005)

(untitled) - Schaller, R. D.; Klimov, V. I. (Phys. Rev. Lett., 2004)

(untitled) - Trinh, M. T.; Houtepen, A. J.; Schins, J. M.; Hanrath, T.; Piris, J.; Knulst, W.; Goossens, A. P. L. M.; Siebbeles, L. D. A. (Nano Lett., 2008)

(untitled) - Schaller, R. D.; Petruska, M. A.; Klimov, V. I. (Appl. Phys. Lett., 2005)

(untitled) - Schaller, R. D.; Sykora, M.; Pietryga, J. M.; Klimov, V. I. (Nano Lett., 2006)

(untitled) - Nair, G.; Bawendi, M. G. (Phys. Rev. B, 2007)

(untitled) - Schaller, R. D.; Sykora, M.; Jeong, S.; Klimov, V. I. (J. Phys. Chem. B, 2006)

(untitled) - Gachet, D.; Avidan, A.; Pinkas, I.; Oron, D. (Nano Lett., 2010)

(untitled) - Murphy, J. E.; Beard, M. C.; Norman, A. G.; Ahrenkiel, S. P.; Johnson, J. C.; Yu, P.; Mićić, O. I.; Ellingson, R. J.; Nozik, A. J. (J. Am. Chem. Soc., 2006)

(untitled) - Schaller, R. D.; Pietryga, J. M.; Klimov, V. I. (Nano Lett., 2007)

(untitled) - Stubbs, S. K.; Hardman, S. J. O.; Graham, D. M.; Spencer, B. F.; Flavell, W. R.; Glarvey, P.; Masala, O.; Pickett, N. L.; Binks, D. J. (Phys. Rev. B, 2010)

(untitled) - Beard, M. C.; Knutsen, K. P.; Yu, P.; Luther, J. M.; Song, Q.; Metzger, W. K.; Ellingson, R. J.; Nozik, A. J. (Nano Lett., 2007)

(untitled) - Allan, G.; Delerue, C. (Phys. Rev. B, 2006)

(untitled) - Franceschetti, A.; An, J. M.; Zunger, A. (Nano Lett., 2006)

(untitled) - Allan, G.; Delerue, C. (Phys. Rev. B, 2009)

(untitled) - Shabaev, A.; Efros, A. L.; Nozik, A. J. (Nano Lett., 2006)

(untitled) - Schaller, R. D.; Agranovich, V. M.; Klimov, V. I. (Nat. Phys., 2005)

(untitled) - Rabani, E.; Baer, R. (Nano Lett., 2008)

(untitled) - Rabani, E.; Baer, R. (Chem. Phys. Lett., 2010)

(untitled) - Govoni, M.; Marri, I.; Ossicini, S. (Nat. Photonics, 2012)

(untitled) - Semonin, O. E.; Luther, J. M.; Choi, S.; Chen, H.-Y.; Gao, J.; Nozik, A. J.; Beard, M. C. (Science, 2011)

(untitled) - Timmerman, D.; Izeddin, I.; Stallinga, P.; YassievichI, I. N.; Gregorkiewicz, T. (Nat. Photonics, 2008)

(untitled) - Timmerman, D.; Izeddin, I.; Gregorkiewicz, T. (Phys. Status Solidi A, 2010)

(untitled) - Timmerman, D.; Valenta, J.; Dohnalová, K.; de Boer, W. D. A. M.; Gregorkiewicz, T. (Nat. Nanotechnol., 2011)

(untitled) - Trinh, M. T.; Limpens, R.; de Boer, W. D. A. M.; Schins, J. M.; Siebbeles, L. D. A.; Gregorkiewicz, T. (Nat. Photonics, 2012)

(untitled) - Giannozzi, P.; Baroni, S.; Bonini, N.; Calandra, M.; Car, R.; Cavazzoni, C.; Ceresoli, D.; Chiarotti, G. L.; Cococcioni, M.; Dabo, I.; Corso, A. D.; de Gironcoli, S.; et al. (J. Phys.: Condens. Matter, 2009)

(untitled) - Govoni, M.; Marri, I.; Ossicini, S. (Phys. Rev. B, 2011)

(untitled) - Marini, A.; Hogan, C.; Grüning, M.; Varsano, D. (Comput. Phys. Commun., 2009)

(untitled) - Rozzi, C. A.; Varsano, D.; Marini, A.; Gross, E. K. U.; Rubio, A. (Phys. Rev. B, 2006)

(untitled) - Marri, I.; Govoni, M.; Ossicini, S. (J. Am. Chem. Soc., 2014)

(untitled) - de Boer, W. D. A. M.; Timmerman, D.; Dohnalová, K.; Yassievich, I. N.; Zhang, H.; Buma, W. J.; Gregorkiewicz, T. (Nat. Nanotechnol., 2010)

(untitled) - Lioudakis, E.; Othonos, A.; Nassiopoulou, A. G. (Appl. Phys. Lett., 2007)

(untitled) - Beard, M. C.; Midgett, A. G.; Hanna, M. C.; Luther, J. M.; Hughes, B. K.; Nozik, A. J. (Nano Lett., 2010)